Burkholderia gladioli strain KJ-34 exhibits broad-spectrum antifungal activity - Yang, Chunnan; Wang, Zhihui; Wan, Jiangxue; Qi, Tuo; Zou, Lijuan (Frontiers in Plant Science, 2023)
The antibiotic activity agents of microbes identified effective to plants pathogens are well documented. KJ-34 is a potential biocontrol bacterium isolated from the rhizosphere soil of rice and could fight multiple fungal pathogens (i.e. Ustilaginoidea virens, Alternaria solani, Fusarium oxysporum, Phytophthora capsica, Corynespora cassiicola). The favoured fermentation conditions are determined and the fermentation broth treatment could significantly inhibit the infection of Magnaporthe oryzae and Botryis cinerea. The fermentation broth suppression ratio is 75% and 82%, respectively. Fermentation broth treatment disrupted the spore germination and leaded to malformation of hyphae. Additionally, we identified the molecular weight of antifungal products were less than 1000 Da through semipermeable membranes on solid medium assay. To search the potentially antifungal molecules that produce by KJ-34, we used the comparative and bioinformatics analyses of fermentation broth before and after optimization by mass spectrometry, Untargeted metabolomics analysis are presumed to have a library of antifungal agents including Ac-Yvad-cho, Benzoylstaurosporine, TAXOL C, Morellin, Jubanine B, Trichostatin A, Thapsigargin, Kabiramide B, Scopolamine, Enniatin B, Latrunculin A, and so on. These results suggest that KJ-34 produced various biological control agents to suppress multiple phytopathogenic fungi and shown a strong potential in the ecological technologies of prevention and protection.